2019
DOI: 10.1002/hed.26029
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal swallowing mechanics associated with upper esophageal sphincter pressure wave

Abstract: Background: Opening of the upper esophageal sphincter (UES) is a critical element of swallowing. Understanding the functional pharyngeal anatomy during UES opening would be clinically useful for dysphagia evaluation and treatment. Methods: Simultaneous high-resolution pharyngeal manometry and videofluoroscopy (VFS) videos for 18 nondysphagic subjects were evaluated. UES pressure readings were segmented into six pressure phases, including a poorly understood pre-relaxation contraction. Anatomic landmarks were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…This suggests that pre-swallow UES basal pressure may be influenced by preparatory central and possible volitional factors. In general, the UES pre-swallow contraction is thought to assist in the creation of negative pressures within the proximal esophagus which, upon UES opening, causes a bolus suction effect that facilitates bolus transfer into the esophagus (18,29,43). This suction effect is associated with negative nadir UES relaxation pressures, a biomechanical feature which was apparent in our participants, particularly during smaller volume swallows.…”
Section: Pharyngeal Ues and Proximal Esophageal Contractility Measuresmentioning
confidence: 76%
See 1 more Smart Citation
“…This suggests that pre-swallow UES basal pressure may be influenced by preparatory central and possible volitional factors. In general, the UES pre-swallow contraction is thought to assist in the creation of negative pressures within the proximal esophagus which, upon UES opening, causes a bolus suction effect that facilitates bolus transfer into the esophagus (18,29,43). This suction effect is associated with negative nadir UES relaxation pressures, a biomechanical feature which was apparent in our participants, particularly during smaller volume swallows.…”
Section: Pharyngeal Ues and Proximal Esophageal Contractility Measuresmentioning
confidence: 76%
“…The oro-pharyngeal swallow response requires complex neuro-regulation (10,13,19,29,32,41,46,58). During volitional swallowing, bolus characteristics such as volume, taste, viscosity and temperature are detected and relayed to the sensory cortex, and brainstem (19).These sensory inputs enable adaptation of the swallow system for optimal bolus transfer from the oral cavity to the esophagus.…”
Section: Introductionmentioning
confidence: 99%
“…The present study is clinically relevant, because it provides useful information on the UES opening during swallowing. In general, the UES opening has been considered as a passive event, because it occurs as a result of the elevation of the hyolaryngeal complex and of the relaxation of the cricopharyngeal part of the inferior constrictor [2,[7][8][9][10][11]. Our findings revealed that the palatopharyngeus spread across the inner surface of the cricopharyngeal part of the inferior constrictor, and it is connected to the cricopharyngeal part of the inferior constrictor thorough a dense connective tissue (Fig.…”
Section: Discussionmentioning
confidence: 69%
“…The opening of the upper esophageal sphincter (UES), which is located on the cricopharyngeal part of the inferior constrictor and the uppermost part of the esophagus [1][2][3][4], is one of the essential events required for proper swallowing [5,6]. In general, the UES opening occurs as a result of the elevation of the hyolaryngeal complex and the relaxation of the cricopharyngeal part of the inferior constrictor [2,[7][8][9][10][11]. Therefore, the mechanism of the UES opening has been considered a passive event, and a few studies have focused on whether any anatomical structures directly act on the UES opening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation